а) (8-5х)-(12-2х)+(6х+2,6)= - 8
8-5х-(12-2ч)+(6х+2,6)= - 8
8-5х-12+2х+6х+2,6= - 8
-1,4-5х+2х+6х= - 8
-1,4+3х= - 8
3х= - 8+1,4
3х= - 6,6
х= - 2,2
б)(3х-6)*(х+2-6)=0
(3х-6)*(х-4)=0
3х-6=0
х-4=0
х=2
х=4
У уравнения 2 решения
х1=2, х2=4
Пошаговое объяснение:
а) (8-5х)-(12-2х)+(6х+2,6)= - 8
8-5х-(12-2ч)+(6х+2,6)= - 8
8-5х-12+2х+6х+2,6= - 8
-1,4-5х+2х+6х= - 8
-1,4+3х= - 8
3х= - 8+1,4
3х= - 8+1,4
3х= - 6,6
х= - 2,2
б)(3х-6)*(х+2-6)=0
(3х-6)*(х-4)=0
3х-6=0
х-4=0
х=2
х=4
У уравнения 2 решения
х1=2, х2=4
Пошаговое объяснение: